Human-insider Threat Analysis for the Purpose of Modeling - Kotsiuba, I.V. (Электронное моделирование, 2016)
This article presents the definition of the insider threat and its impact; it also provides an overview of techniques to control and remediate these threats. Дано определение инсайдерской угрозы и рассмотрены ее воздействия. Представлен обзор методов контроля и способов устранения этих угроз.